Environmental quality, residents health, and economic growth in the Yellow River Basin - Yan, Xiaohan; Chin, Lee; Abdul Samad, Abdul Rahim; Muhamad Senan, Mohamad Khair Afham; Ding, Yemin (Springer, 2023)
The Yellow River Basin (YRB) is one of the most important economic and environmental regions in China. With a growing population and expanding industries, the region is encountering signifcant challenges related to economic development, environmental quality, and residents health. The current study aimed to explore the key drivers and barriers to sustainable development in the region by applying a comprehensive measure of environmental quality, namely the water-energy-food nexus coordination and coupling degree (WEF-CCD), to analyze nine YRB provinces. The measure encompassed the interdependencies between water, energy, and the food sector, providing a holistic assessment of the environmental capacity in the region. The analysis demonstrated that environmental quality varies signifcantly among the nine YRB provinces. Subsequently, panel structural vector auto-regression (PSVAR) was conducted to determine the inter-relationships between environmental quality, economic growth, and residents health status in the YRB. The PSVAR analysis revealed that the YRBs expanding economic growth is detrimental to the environment. The rise of healthcare expenditures also negatively impacts the economy and the environment. Nonetheless, environmental quality was not found to be a contributing factor to economic development and public health at the current stage. Based on the fndings, policies promoting resource efciency and coordination, clean technologies, and preventative healthcare practices could assist in reducing the negative environmental impacts of economic growth while promoting long-term economic sustainability in the YRB.